An evaluation of client's perception of facilities management (FM) contract service delive [electronic resource] - 512944 Abdul Rahman Putera Ahmad Jaseh (2011)
Thesis (Sarjana Sains (Pengurusan Aset dan Fasiliti)) - Universiti Teknologi Malaysia, 2011